2020
DOI: 10.1159/000510715
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness Changes after Orthokeratology Lens Wearing in Young Adults with Myopia

Abstract: Introduction: Recently in South Korea, there are increasing number of young adults undergoing orthokeratology treatment for myopia control. They prefer orthokeratology treatment more than wearing spectacles or having a refractive surgery for several reasons. However, there is little research on the effect of orthokeratology treatment on choroids. Objective: The aim of this study was to analyze the change in choroidal thickness (CT) in the horizontal axis in young myopic adults after orthokeratology treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…Increased ChT has been associated with reduced eye growth [ 27 , 28 ] and so may have played a role in the reduced eye growth recorded in MOK-treated eyes over the course of the study. The reduced ChT that we observed in OK-treated eyes is contrary to the findings of most other studies, which report increases in choroidal thickness with conventional orthokeratology [ 22 , 29 ]. The reason for this inconsistency is not clear, although other studies have typically employed optical coherence tomography (OCT) to assess choroidal thickness, whereas we used ocular biometry (Lenstar) measures in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Increased ChT has been associated with reduced eye growth [ 27 , 28 ] and so may have played a role in the reduced eye growth recorded in MOK-treated eyes over the course of the study. The reduced ChT that we observed in OK-treated eyes is contrary to the findings of most other studies, which report increases in choroidal thickness with conventional orthokeratology [ 22 , 29 ]. The reason for this inconsistency is not clear, although other studies have typically employed optical coherence tomography (OCT) to assess choroidal thickness, whereas we used ocular biometry (Lenstar) measures in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Over the one-year follow-up period, the study found that the SFChT became thicker in both eyes after orthokeratology, as was also reported in other studies [ 10 , 11 , 21 ]. Recent studies have suggested that the SFChT would change after orthokeratology lens wearing [ 22 , 23 ], with a significant thickening of the temporal choroid in the subfoveal area, but not in the nasal side [ 12 ].…”
Section: Discussionsupporting
confidence: 85%
“…Optical coherence tomography (ZEISS CIRRUS HD-OCT-5000) was used to measure the ChT of the subjects; the head position was fixed during the whole measurement. The “HD CROSS” test method and Enhanced Deep Imaging (EDI) mode were selected for standardized measurements [ 10 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After wearing orthokeratology lenses for a period as short as 3 to 4 weeks, myopic patients exhibited choroidal thickening. Further, after close-range reading for a short period, choroidal thickness is decreased [ 9 11 ]. This indicates that choroidal mechanisms are involved in regulating the refractive error in the human eye.…”
Section: Introductionmentioning
confidence: 99%